Short Total Synthesis of (±)‐γ‐Lycorane by a Sequential Intramolecular Acylal Cyclisation (IAC) and Intramolecular Heck Addition Reaction. Issue 20 (20th March 2017) - Monaco, Alessandra; Szulc, Blanka R.; Rao, Zenobia X.; Barniol‐Xicota, Marta; Sehailia, Moussa; Borges, Bruno M. A.; Hilton, Stephen T.
Abstract: An intramolecular acylal cyclisation (IAC) approach to the synthesis of a range of bicyclic heterocycles is reported. As an example of the utility of the IAC reaction, the methodology was applied in a protecting‐group‐free five‐step total synthesis of (±)‐γ‐lycorane, incorporating a new intramolecular Heck addition reaction to generate the pentacyclic core structure of the natural product in good yield. Abstract : Tandem cyclisation : The pentacyclic structure of the natural product (±)‐γ‐lycorane was synthesized by a new sequential Lewis acid mediated intramolecular acylal cyclisation (IAC)/Heck coupling approach. By using this methodology, a range of bicyclic heterocycles was also synthesized in good yields demonstrating the potential of the IAC reaction to access complex heterocycles (see scheme).